PENGARUH KETERAMPILAN METAKOGNISI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA MELALUI METODE PEMBELAJARAN DISCOVERY - Ria Herpiana; Undang Rosidin; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
The purpose of this research to determine: (1) the influence of the metacognition skills of students are learning physics IPA by using discovery method; (2) the influence of the motivation learning of students are learning physics IPA by using discovery method; (3) the influence of the metacognition skills and motivation learning of students are learning physics IPA by using discovery method. The population is all of students in class VIII SMPN8 Bandar Lampung. The sample are students of class VIIIB amount 39 students. The sample class is selected by purposive sampling. Design of this research is one-shot case study. The results are: (1) there are influence of the metacognition skills of students are learning physics IPA by using discovery method and it contributed 15%; (2) there are influence of the motivation learning of students are learning physics IPA by using discovery method and it contributed 27%; (3) there are The influence of the metacognition skills and motivation learning of students are learning physics IPA by using discovery method and it contributed 32%.Kata kunci: hasil belajar, metakognisi, metode discovery, motivasi